The Consequences of Bullying: Analyzing Its Effects on Student Achievement and Psychological Well-Being - M, Syahruddin; Pongpalilu, Fien; Aisyah, Sitti; Maing, Rosmawati Abdul; Purnamasari, Feby (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Bullying has become a widespread issue in schools, with significant consequences for the victims. This study aims to explore the detrimental effect of bullying on students' academic achievement and stress levels. the study used mixed method approach, combining quantitative and qualitative data.A quantitative approach was employed, with data collected from 223 students at SMA Negeri 1 Pangkep using a Likert scale instrument. The findings reveal that bullying behavior, which encompasses students' thinking, feelings, attitudes, actions, and responsibility, is generally in the